24. KNOWLEDGE AND PRACTICES ON ROUTINE HAND HYGIENE COMPLIANCE OF NURSES AND MIDWIVES IN THE HOSPITAL OF QUANG NGAI MATERNITY AND PEDIATRIC HOSPITAL 2023 (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the knowledge and practice of compliance with routine hand hygiene and identify some factors related to the knowledge and practice of routine hand hygiene compliance of nurses and midwives at different departments. Clinical, Obstetrics and Pediatrics Hospital, Quang Ngai Province in 2023. Research method and time: The study applied an analytical cross-sectional research method and was implemented from 9/2022 to 9/2023 with 110 nurses and midwives, observation by checklist and knowledge distribution. Apply descriptive statistics (frequency, percentage) and analytical statistics (test χ2, OR, 95%CI with significant level at p
Keywords: Knowledge, practices, routine hand hygiene, Obstetrics - Pediatrics Hospital, Quang Ngai.